2019
DOI: 10.5811/westjem.2019.7.42731
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does the Standardized Video Interview Score Correlate with Traditional Interview Performance?

Abstract: IntroductionIn 2017, all medical students applying for residency in emergency medicine (EM) were required to participate in the Standardized Video Interview (SVI). The SVI is a video-recorded, uni-directional interview consisting of six questions designed to assess interpersonal and communication skills and professionalism. It is unclear whether this simulated interview is an accurate representation of an applicant’s competencies that are often evaluated during the in-person interview.ObjectiveThe goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Another example of the programs' efforts to improve and ease the interview process is using the virtual systems. However, the comparison of standardized video interviews (SVI) to traditional in-person interviews was recently investigated by two studies, and they both found a positive correlation between SVI and in-person interview scores [ 15 , 16 ]. In addition, Husain et al investigated how SVIs affect an applicant's likelihood to be invited for an interview.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of the programs' efforts to improve and ease the interview process is using the virtual systems. However, the comparison of standardized video interviews (SVI) to traditional in-person interviews was recently investigated by two studies, and they both found a positive correlation between SVI and in-person interview scores [ 15 , 16 ]. In addition, Husain et al investigated how SVIs affect an applicant's likelihood to be invited for an interview.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two of these studies evaluated the standardized video interview (SVI), an online unidirectional interview that was developed by the Association of American Medical Colleges (AAMC) and piloted with the Accreditation Council for Graduate Medical Education (ACGME)-accredited emergency medicine programs. Twelve of these studies were abstracts [ 38 – 49 ] and 10 were articles [ 50 59 ]. Applicants submitted an audio/video response to six questions which was subsequently scored from 6 to 30.…”
Section: Resultsmentioning
confidence: 99%
“…Granted, there was no standardization in what the faculty asked, and they were not blinded to academic performance of the applicants [ 36 ]. While there was an evaluation of six emergency medicine programs that demonstrated a positive linear correlation between the SVI score and the traditional interview score, it was a very low r coefficient; thus the authors concluded that the SVI was not adequate to replace the interview itself [ 37 ].…”
Section: Introductionmentioning
confidence: 99%